Financial literacy and gender differences: Women choose people while men choose things? - Sigurður Guðjónsson; Inga Minelgaite; Kari Kristinsson; Sigrún Pálsdóttir (Administrative Sciences, 2022)
According to gender personality traits, women are more interested in people, whereas men are more interested in things. The goal of this research is to see if there is a gender gap in financial literacy and if these disparities can be explained by different areas of interest. A convenience sample of nearly a thousand responses was received in quantitative research. The findings clearly show that women have lower financial literacy than men, but there is no indication that this is due to men and women's differing interests in people and things.
Keywords: 350; financial literacy; gender differences; personality traits